Prospective evaluation of a preoperative biomarker panel for prediction of upstaging at radical cystectomy. (January 2014) - Shariat, Shahrokh F.; Passoni, Niccolo; Bagrodia, Aditya; Rachakonda, Varun; Xylinas, Evanguelos; Robinson, Brian; Kapur, Payal; Sagalowsky, Arthur I.; Lotan, Yair
Abstract : Objectives: To prospectively test whether a panel of biomarkers could identify patients with organ‐confined disease likely to be upstaged at radical cystectomy (RC), as retrospective studies have found that cell‐cycle‐ and proliferation‐related biomarkers can help improve prognostic accuracy after RC. Patients and Methods: We prospectively performed p53, p21, p27, Ki67, and cyclin E1 immunohistochemical staining on transurethral resection of the bladder (TURB) specimens from 87 patients treated with RC for organ‐confined urothelial carcinoma of the bladder (UCB). The number of altered biomarkers was categorised as 'favourable' (≤2 altered markers) or 'unfavourable' (>2). Results: Expression of p53, p21, p27, cyclin E1, and Ki67 were altered in 61 (70%), 19 (22%), 26 (30%), four (5%), and 70 (80%) patients, respectively. The median number of positive markers was two. In all, 47 (54%) patients were upstaged when T‐stage was considered alone and 49 (56%) when T‐ and/or N‐stage were considered both as upstaging. In multivariable analyses that adjusted for the effects of age, clinical stage, concomitant carcinoma in situ, and time from TURB to RC, an 'unfavourable' biomarker score was independently associated with T‐stage upstaging (hazard ratio [HR] 3.3, P = 0.024) but not T‐ and/or N‐stage upstaging (HR 2.76, P = 0.06). Addition of p27, number of positive markers, and biomarker score each increased the discrimination of a base model for prediction of T‐stage upstaging (5%, 6%, and 5%, respectively) and T‐ and/or N‐stage upstaging (4%, 6%, and 3%, respectively). Conclusions: Cell‐cycle‐ and proliferation‐related markers in the TURB specimen improve the prediction of upstaging at RC. Such a marker panel may help identify patients with non‐muscle‐invasive UCB who are clinically under‐staged needing RC and patients with muscle‐invasive UCB who are likely to be non‐organ‐confined thereby potentially benefiting from neoadjuvant chemotherapy.